The impediments in adopting the environmental management system (EMS) implementation among local authorities in Malaysia / Nero Madi, Corina Joseph and Mariam Rahmat - Madi, Nero; Joseph, Corina; Rahmat, Mariam (Faculty of Accountancy, 2016)
The Government has introduced five major initiatives to transform the nation, namely, 1 Malaysia, the New Economic Model (NEM), the Government Transformation Programme (GTP), the Economic Transformation Plan (ETP), and the Tenth Malaysia Plan (Annuar, 2011). The NEM lists eight Strategic Reform Initiatives (SRI) to drive the Malaysian economy towards high income, inclusive and sustainable economy. One of the initiatives is strengthening the public sector via numerous reform agenda, such as implementing environmental management system (EMS). In this study, local authorities were chosen as a sample because of their important role in advancing towards sustainable development. Moreover, only three out of 149 local authorities in Malaysia to date have implemented EMS. The three local authorities are Dewan Bandaraya Kuching Utara (DBKU), Majlis Perbandaran Seberang Perai (MPSP), and Majlis Perbandaran Pasir Gudang. (MPPG). Hence, the study inten orities. The survey instrument was developed based on the results from Joseph et al. (2014), which was distributed via mail to all 146 local authorities in Malaysia. It was expected that the findings would be used to encourage the use of ISO 14001 as a tool for implementing sustainability agenda as practised in other countries, as well as to promote the use of EMS to address the requirement for a plan to implement sustainable development programme, such as Local Agenda 21. It was also expected that the survey findings would fill in the gaps in the literature in better understanding the ISO14001 adoption stage.